Aquisição de conceitos psicomotores pelo aluno surdo: avaliação de um programa de ensino - Fenske, Sheila Glaucieli (2008)
Psycomotricity has presented relationship with several areas of learning. Starting from that, this study has three objectives: elaborate, implement and evaluate the effectiveness of a teaching program based on motor activities that emphasizes the body scheme and the space perception, in order to investigate the influence of it in the acquisition of corporal and space concepts for the deaf student. Three deaf students, between seven and nine years old, from a public school of Sao Paulo s interior were chosen to participate in the research. The participants' selection was accomplished following indications of Municipal General Office of Education and Municipal General office of Health. The design research used was intra-subject in multiple baseline. The program of activities was adapted to the results presented by the participant in the motor evaluation and in the baseline. Planned activities were applied in intervention phase, with conceptual and motor evaluation among each one of the stages and a final evaluation of both after the end of them. Three answer levels were used for each expected motor behavior according to each age as learning criterion. To analyze the results of motor and conceptual evaluations, three aspects were considered: the diary of the researcher's field, the socioeconomic questionnaire and the applied questionnaire in the students' parents. These results suggest that improvement in psycomotricity was more strong for the space perception than for the body scheme and if there s any modification in right and left notions, these are transposed for the graphic expression. It was also verified that suggested education does not have the waited success for the body scheme. One of the possible justifications is the necessity of more time in intervention.